Decolonizing the Study of Religions:Muslim Intellectuals and the Enlightenment Project of Religious Studies - Abdulkader Tayob (Journal for the Study of Religion)
The term ‘religion’as a discursive term occupies a dominant, but neglected feature of Muslim intellectual reflections since the 19thcentury. Intellectuals from Mu?ammad ?Abduh (he diedin 1905) to recent scholars like Na?r ??mid Ab? Zayd (he diedin2010) have used religion as a critical term to develop a critique of tradition and modernity, and a strategy for renewal. This discourse may becompared with the study of religion since the 19thcentury that has also used religion to develop a perspective on the religious history of humankind. In this contribution, I argue that the two intellectual traditions that have employed religion–Kantian and the modern Islamic–point to very different ways of relating to the world, to the self and the ‘other’, and to the political condition of modernity. Rather than using the hegemonic Western tradition to make a judgment on the modern Islamic, I use the latter to point to the former’s peculiar proclivities. Using the modern tradition among Muslim intellectuals, I invite an inquiry into both from each other’s positions.